Ecce homo General Idea drawings, 1985-1993 - Bronson, AA 1946-; Bovier, Lionel 1970-; Gilman, Claire (JRP Editions, 2022)
Focusing on one specific and lesser-known aspect of the manifold practice of General Idea, the Canadian collective founded in Toronto in 1969 by Felix Partz, Jorge Zontal and AA Bronson, this volume highlights their drawing practice, with generous insight into 125 carefully selected drawings realized between 1985 and 1993--the period the collective spent in New York. The publication's design is inspired by George Grosz's legendary Ecce Homo album (1922-23) because, as Bronson says, "the anti-Semitism in Grosz's narrative is mirrored by the homophobia in ours." Investigating motifs in the group's multimedia works, such as poodles, stiletto heels, masks, heraldry and metamorphosed genitalia, these drawings were primarily produced by Zontal during group meetings. However, given General Idea's mandate for coauthorship, as well as the circumstances under which they were executed, the drawings are considered to be collaborative. The repetition of motifs follows a viral logic akin to General Idea's own penchant for mass reproduction. Together, these drawings are a fascinating window into General Idea's unique notions of collaboration and coauthorship, and their singular and innovative approach to art and drawing
Includes index of works
Imprimt: This book is published on occasion of the exhibition "Ecce Homo. The Drawings of General Idea, 1985-1993", at The Drawing Center, New York (October 7, 2022 - January 15, 2023) and at MAMCO Geneva (February 22 - June 18, 2023). Curated by Clair Gilman and Lionel Bovier
Booklet includes an essay by Claire Gilman and a converation with AA Bronson by Claire Gilman and Lionel Bovier
Keywords: Bronson, AA -- 1946-; General Idea -- Künstlervereinigung; Geschichte 1985-1993; Sammlung; Zeichnung; New York, NY; General Idea (Firm) / Exhibitions; Drawing, Canadian / 20th century / Exhibitions; Bronson, AA / 1946-; General Idea / Expositions; Dessin canadien / 20e siècle / Expositions; General Idea (Firm); Drawing, Canadian; 1900-1999; Exhibition catalogs; Ausstellungskatalog -- Drawing Center -- 07.10.2022-15.01.2023 -- New York, NY; Ausstellungskatalog -- Mamco, Musée d'art moderne et contemporain -- 22.02.2023-18.06.2023 -- Genf; Bildband